HUBUNGAN INTENSITAS PENGGUNAAN APLIKASI TIKTOK TERHADAP MOTIVASI BELAJAR SISWA KELAS V SD NEGERI RIUNGGUNUNG - Maulana, Rijkar; Hilman Hilmawan; Nurani Hadnistia Darmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the increasing use of the TikTok application among elementary school students, which has the potential to influence their learning motivation. The purpose of this study was to determine the intensity of TikTok application usage, students’ learning motivation, and the relationship between TikTok usage intensity and the learning motivation of fifth-grade students in Indonesian language subjects at SD Negeri Riunggunung. This study employed a quantitative approach with a correlational method. The population consisted of all fifth-grade students at SD Negeri Riunggunung, totaling 28 students, using a saturated sampling technique. Data were collected using questionnaires and analyzed using descriptive statistics and Pearson Product Moment correlation with SPSS. The results showed that TikTok usage intensity was categorized as moderate, while learning motivation was categorized as good. The Pearson correlation coefficient (r) was 0.387 with a significance value of 0.042 < 0.05, indicating a positive and significant relationship. The coefficient of determination (R²) was 0.149, meaning TikTok usage intensity contributed 14.9% to students’ learning motivation. In conclusion, TikTok application usage has a positive and significant relationship with students’ learning motivation, though the strength is categorized as low.